2020
DOI: 10.1111/neup.12706
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline prevents depression‐like behavior in streptozotocin‐induced diabetic mice

Abstract: Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia. Diabetic patients are known to have a higher prevalence and a higher risk of depression compared with the general population. The pathogenesis of diabetes-related depression is unclear, and the treatment is not well-established. Therefore, the prevention of diabetes-related depression is important for improving the quality of life of diabetic patients. Minocycline, a secondgeneration tetracycline antibiotic, has recently gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
6
0
2
Order By: Relevance
“…In this study, diabetic control animals displayed marked decreases in body weight and increases in blood sugar level, with motor signs such as significant decreases in the number of efficient steps without tremor (good steps) in the HGT, as well as decreases in time spent on the horizontal grid, possibly due to muscle fatigue associated with the systemic disease [ 40 , 41 ]. Other authors reported similar observations in STZ-induced diabetic rodents [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 77%
“…In this study, diabetic control animals displayed marked decreases in body weight and increases in blood sugar level, with motor signs such as significant decreases in the number of efficient steps without tremor (good steps) in the HGT, as well as decreases in time spent on the horizontal grid, possibly due to muscle fatigue associated with the systemic disease [ 40 , 41 ]. Other authors reported similar observations in STZ-induced diabetic rodents [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 77%
“…Bu çalışmada, daha önce yapılan çalışmalarla benzer biçimde DM grubunun zorunlu yüzme testinde geçirdiği hareketsiz sürenin kontrol grubuna göre anlamlı olarak arttığı gösterilmiştir [15,17,18].…”
Section: Sonuç Ve Tartişmaunclassified
“…Minosiklinin deneysel iskemik felç sonrası meydana gelen depresyon ve anksiyete üzerine etkisinin incelendiği bir çalışmada, minosiklinin (30mg/kg, i.p., 14 gün) lokomotor aktiviteyi değiştirmeksizin antidepresan-benzeri etkiler gösterdiği bildirilmiştir [23]. STZ ile diyabet oluşturulan farelere kronik olarak uygulanan (4 hafta) minosiklinin (100mg/kg, p.o) zorunlu yüzme testinde geçirilen hareketsiz zamanı azalttığı, bu etkinin proinflamatuar sitokin düzeyi ve mikroglial aktivasyonun azalması yolu ile ortaya çıktığı bildirilmiştir [18].Başka bir çalışmada da benzer biçimde STZ uygulanarak diyabet oluşturulan ratlarda kronik minosiklin (80mg/kg, p.o., 3 hafta) tedavisi ile zorunlu yüzme testinde geçirdikleri hareketsiz zamanın azaldığı gösterilmiştir [24].…”
Section: Sonuç Ve Tartişmaunclassified
“…[12][13][14][15] There is profound evidence for antidepressant effects of minocycline in animal models, 16 most likely mediated through beneficial effects on microglial activation. [17][18][19][20] Thus, minocycline treatment has been suggested as a novel antidepressant approach 21 and indeed, a few small randomized clinical trials (RCTs) suggest antidepressant efficacy of minocycline in MDD patients. 22 Emadi-Kouchak and colleagues showed that patients with HIV with mild-to-moderate depression who underwent a 6-week treatment with 100 mg minocycline exhibited larger improvement of depressive symptoms compared with the placebo group.…”
Section: Introductionmentioning
confidence: 99%
“…Minocycline is a tetracycline antibiotic with pleiotropic antineuroinflammatory properties that readily crosses the blood-brain barrier, inhibits proinflammatory microglial activation, enhances neuroprotective retinoid signaling, and exerts overall neuroprotective effects . There is profound evidence for antidepressant effects of minocycline in animal models, most likely mediated through beneficial effects on microglial activation . Thus, minocycline treatment has been suggested as a novel antidepressant approach and indeed, a few small randomized clinical trials (RCTs) suggest antidepressant efficacy of minocycline in MDD patients .…”
Section: Introductionmentioning
confidence: 99%